2016
DOI: 10.1186/s40662-016-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

High intercorneal symmetry in corneal biomechanical metrics

Abstract: BackgroudTo evaluate the symmetry of corneal biomechanical metrics, measured using an ocular response analyzer (ORA) and self-built corneal inflation test platform, in bilateral rabbit corneas and to investigate their relationship with physical intraocular pressure (IOPp).MethodsTwenty fresh enucleated eyes from ten rabbits were used for ex vivo whole ocular globe inflation. IOP was increased from 7.5 to 37.5 mmHg with 7.5 mmHg steps and biomechanical metrics were acquired using the ORA. At least 3 examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…A comparison of eyes from the same human is based on the assumption of microstructural and topographic symmetry [13,14,[22][23][24]. Elsheikh et al [12] found qualitative evidence of similarity in the corneal behavior of porcine eyes.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of eyes from the same human is based on the assumption of microstructural and topographic symmetry [13,14,[22][23][24]. Elsheikh et al [12] found qualitative evidence of similarity in the corneal behavior of porcine eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to evaluate the level of interocular corneal symmetry in the normal healthy population by analyzing a great variety of parameters provided by different commercial devices used for such purpose [8][9][10][11][12][13][14][15]32,[36][37][38][39]. Specifically, high levels of interocular symmetry have been reported in variables such as corneal curvature [9,10,12,37], central corneal thickness [9,13,37,38], anterior and posterior corneal elevation [10,12,38], corneal astigmatism [9,11,36,39], minimum corneal thickness [10,12,13], corneal aberrations [14], corneal diameter [15], corneal shape factor [37], and even some biomechanical metrics [40]. This is consistent with the results obtained in our sample, as we did not find significant differences between fellow eyes in corneal asphericity, aberrations, pachymetry, and volume.…”
Section: Discussionmentioning
confidence: 99%
“…Using ORA, Zheng et al [22] demonstrated an obvious symmetry of CH and CRF in bilateral rabbit corneas. We also identified two asymmetrical parameters in the sample, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations of interocular symmetric biometry were consistent with previous studies [ 19 21 ]. Using ORA, Zheng et al [ 22 ] demonstrated an obvious symmetry of CH and CRF in bilateral rabbit corneas. We also identified two asymmetrical parameters in the sample, i.e.…”
Section: Discussionmentioning
confidence: 99%